The evaluation, management and cost of chronic cough in immunocompetent Filipino adults consulting pulmonary specialist clinics - David-Wang, Aileen S.
Background. Chronic cough, defined cough persisting for at least three weeks, is a common diagnostic and therapeutid problem. It is associated with a marked deterioration in quality of life which returns to normal on successful treatment. Higher success rates have been reported when a systematic investigational protocal is used. A concensus panel report by the American College of Chest Physicians (ACCP) was published in 1998. Its applicability to the local setting has not been tested. No major study has addressed its etiologies in the Filipino patient. The cost of treating chronic cough is also unknown. Objective of the Study. We determined the applicability of the ACCP Anatomic Diagnostic Protocol in the evaluation and management of chronic cough among immunocompetent adults, in terms of the degree of compliance of pulmonary specialists to its key components, the affordability and availability of the recommended laboratory investigations and treatments, the identification of specific etiologies, and the measurement of response to recommended specific therapies. We also developed a modified algorithm of the ACCP protocol which was tailored to local needs and concerns. Subjects and Methods. Unselected adult patients, age [greater than equal] 18 years, who consulted at or were referred to the pay and charity pulmonary clinics of a university teaching hospital (Philippine General Hospital, Manila) between January 2003 and December 2004 for cough persisting for at least 3 weeks were included in the study. Immunocompromised patients were excluded. An ambispective study design was employed. Historical data on the characteristics of cough, past medical history, prior consults, treatment and expenses incurred were collected retrospectively or were available from records and then the cohort was followed up and the physical findings, subsequent diagnostic tests, drug therapy, repsonse to treatment, and expenses subsequently incurred were determined up to two months from the first visit. A 19-item yes-or-no compliance checklist to assess adherence to the key components of the protocol was developed and pre-tested and each evaluable patients encounter was assessed independently by 3 board-certified pulmonologists. An overall compliance score for each patient is the sum of the number of items with 'yes' response/ the total applicable items. The assessment of compliance was the result of the concurrence of at least 2 pulmonologists. The final diagnosis for eash patient was based on historical information, physical findings, laboratory examinations and the response to specific therapy directed at the identified etiology. Clinical response was assessed as successful (cough resolved or significantly improved) or failed (cough improved minimally, worsened or failed). Direct costs arising from consultations, laboratory examinations and drug therapy were computed as well as indirect costs arising from time lost from work.
Statistical Analysis. Data encoding and statistical analyses were accomplished using Epi Info version 6 and Stata 7. Frequencies, means [plus minus] SD, modes, medians, ranges and percentile ranks were obtained. The 95% confidence intervals of the means of compliance and costing data were likewise calculated. Differences between groups were compared with Student t test for 2-groups analyses and ANOVA fof [greater than]2-group analyses of continuous variables, and n2 analysis, for categorical varialbles. For the costs with markedly skewed data, the Kruskal-Wallis of medians was measured through the Mann-Whitney-Wilcoxon rank-sum test. Risk ratios and their 95% confidence intervals were measured to predict clinical outcome and to test associations. Sensitivity analysis for economic evaluation was likewise performed. All tests were performed at level of significance, a, p = 0.05. Sample Size Calculation. Assuming compliance to the ACCP Anatomic Diagnostic Protocol is achieved in only 10% of patients and using the formula: N = [P(1-P)/CI2]xf(1-L), where N = number of patients with chronic cough to be studied; P = expected compliance rate; f(1-L) = 3.84; and CI = width of the interval of 5 and considering further a sampling design clustering effect of patients (to a specific physician) of 1.5 and multiplying this to the estimated sample size, the required number of evaluable subjects is 209. To cover for an estimated "lost to follow up" rate of 20%, the minimum sample size should be 251.
Results. 284 patients, representing 287 patient-encounters, were enrolled into the study. 50 (17% of total subjects) were lost to follow up. 237 patients were evaluable. 61.3% were females, with mean age of 50.18 [plus minus] 18.69 years. The mean duration of cough was 22.2 [plus minus 55.64 weeks. The overall compliance rate to the key components of the ACCP protocol was 84% (plus mimus 11.71). This was not influenced by the frequency of identified etiologies per patient. Higher compliance rates were observed when the final diagnosis was pulmonary malignancy, pulmonary tuberculosis and ACE-induced cough and lowest for post-infectious cough. The compliance rates to the individual key components of the algorithm varied widely. Compliance rates of 99-100% were notedfor the conduct of the clinical examination, appropriateness of the basis for the presumptive diagnoses, the prescribed drug therapy for a specific etiology and the evaluation of specific treatment, and the adequacy of clinical response assessment. The evaluation and management of patients with multiple presumptive diagnoses was also highly appropriate. The major deviations stemmed from the use of empiric drug therapy without confirmatory laboratory testing in 70% of patients and the use of non-specific cough therapy at the outset, even when a specific etiology had been identified, in 40% of patients. These deviations were highest among patients with GERD, PNDS and asthma. The causes of cough were determined in 236 out of 237 (99.5%) evaluable patients. Asthma (33.3%), postnasal drip syndrome (30.4%), pulmonary tuberculosis (20.3%), postinfectious cough (15.2%) and COPD/chronic bronchitis (10.1%) were the most common etiologies. GERD was found in only 3.8% of patients. A single diagnosis was found to explain cough in the majority of patients (67.5%). Treatment was judged successful in 63% of patients whose cough resolved completely in 3.20 [plus minus] 2.38 weeks and in 32.5% of patients whose cough reported significant improvement in 3.9 [plus minus] 2.59 weeks. The overall treatment failure rate was 4.6%. Treatment failure was found to be related to non-compliance of the patients, significant lung structural abnormalities that cannot be expected to reverse and terminal illness, rather than to the failure of the evaluation and management process. The outcome of treatment was not influenced by the overall compliance rate (RR=0.99[99% CI: 0.94, 1.061]) and the use of empiric drug treatment (RR= 0.99 [95% CI: 0.93, 1.061]). Some laboratory tests recommended by the protocol were not locally available, including bronchoprovocation test and 24-hour esophageal pH monitoring. On the average, each patient spent P 6,569.81 (95% CI: 5,789.26, 7,350.36) while seeking relief for chronic cough. Two-thirds of this amount was due to expenses incurred from drug therapy. A patient spent a mean P 4,327.37 (95% CI: 3,977.44, 4,677.29) during the study period. A failed treatment was more expensive than a successful therapy.
Vita.
Thesis (MS Epidemiology, Clinical)--University of the Philippines Manila.
Keywords: Cough; Pulmonary medicine; Chronic Disease